EMPOWERING COMMUNITIES FOR SUSTAINABLE TRANSITION: INTEGRATING TOURISM WITH ECONOMIC AND SOCIODEMOGRAPHIC DYNAMICS IN POST-MINING STRATEGIES - Agung Dwi SUTRISNO; Chun-Hung LEE; Sapta SUHARDONO; I Wayan Koko SURYAWAN (Geo Journal of Tourism and Geosites)
This research examines the complex interplay among community empowerment, economic development, and sociodemographic factors in tourist post-mining development. Using a comprehensive methodological approach, we collected and analyzed data from 420 households in Bantar Karet Village, Nanggung Subdistrict, Bogor Regency, West Java Province, Indonesia. Structural Equation Modeling (SEM) explored how economic incentives, community empowerment, and customized engagement strategies based on educational and income levels impact community readiness to support sustainable transitions from mining to tourism. The findings underscore the importance of investing in human capital, primarily through targeted educational programs to enhance skills necessary for environmental stewardship and tourism-related activities. The study advocates for integrated development policies promoting economic, educational, and environmental sustainability in tourism. Policymakers are encouraged to create multidimensional, cooperative, and participatory interventions that align with the community's diverse needs. The research highlights the necessity for continuous monitoring, evaluating, and promoting sustainable tourism-based livelihoods as alternatives to mining dependency. This shift reflects a broader move towards resilience and long-term environmental conservation within the community.